Community awareness and perception of the implementation of the Coastal Resource Management Programs in Bolinao, Pangasinan, Philippines - Tenoso, Annie Rose D.; Paz-Alberto, Annie Melinda (2012)
Community knowledge, involvement, and support are all essential in the implementation of coastal resource management programs for sustainable resource use and economic development. This study aimed to identify the coastal resource management (CRM) programs implemented in Balingasay, Arnedo, Victory and Binabalian in Bolinao, Pangasinan, Philippines, CRM related issues and problems, and the recommended solutions for better management strategies of coastal resources and to determine the extent of community awareness and involvement and perceived government and non-government interventions in the implementation of these programs in these barangays. Marine protected areas and community based mangrove conservation projects were observed to be protected and managed by the local government units and non-governmental organizations.
The respondents had moderate awareness and moderate perceived level of implementation on information, communication and education programs for CRM programs, fisheries and CRM legislation. Similarly, the local communities had moderate awareness and moderate perceived level of implementation of the CRM programs. The perceived level of community participation and involvement in CRM and perceived level of government intervention were found to be occasional. Moreover, the perceived level of interventions of the NGO, academic and research institutions in CRM of Bolinao, Pangasinan were seldom. Low catch by the fisher folk, poverty, overfishing, illegal fishing, pollution, squatting, waste disposal and climate change were the major problems identified. These were caused by different human activities in the coastal area. Provision of alternative livelihood and effective enforcement of fishery laws and ordinances are suggested in order to solve these problems.
Keywords: Coastal resource managemet; Coastal resource managemet -- Bolinao (Pangasinan)